Choice of the victim as the informative sign by working out of the psychological profile of the serial sexual criminal - Fourmanov, Igor A.; Metlickij, Igor E. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
In article on the basis of the analysis modern psychologicals and criminalistics approaches, application prospects uses profiling in a context of psychological maintenance of professional work of employees of law enforcement bodies are considered. The uniform approach to understanding of phenomena «psychological model of the person of the criminal», «a psychological portrait of the criminal» and «a psychological profile of the criminal», proceeding from that functional loading which they bear in criminalistics and legal psychology is offered. Mechanisms of a choice of a victim by the unorganized, mixed and organised serial criminal, proceeding from features of its person are described. Necessity of the account of a choice of a victim of a crime is theoretically proved at drawing up of a psychological profile of the serial criminal.
Keywords: psychological profiling; criminal profiling; the serial criminal; a victim of a crime